Können intensive Beratungsprogramme soziale Ungleichheit beim Übergang in die Hochschule reduzieren? Ergebnisse eines Feldexperiments; Do Intensive Guidance Programs Reduce Social Inequality in the Transition to Higher Education? Results of a Field Experiment; Les programmes de conseil intensif peuvent-ils réduire les inégalités sociales dans la transition vers l'université ? Résultats d'une expérience de terrain - Melinda Erdmann; Irena Pietrzyk; Marcel Helbig; Marita Jacob; Stefan Stuth (Schweizerische Zeitschrift für Soziologie, 2022)
Im Beitrag wird die Wirkung eines intensiven Beratungsprogramms zur Förderung der Studienaufnahme von Hochschulzugangsberechtigten untersucht. Mittels Daten aus einer experimentellen Panelstudie werden der durchschnittliche Effekt auf die Studienaufnahme direkt nach dem Abitur und die Effektheterogenität nach Bildungsherkunft überprüft. Es zeigt sich keine positive Wirkung der Teilnahme. Diese Ergebnisse werden in Bezug auf die ungleichheitsreduzierenden Potentiale individueller Beratung in Deutschland diskutiert. – – This paper examines the effect of an intensive counseling program to promote college access of students who are eligible for college. Using data from an experimental panel study, we examine the average effect on university enrollment directly after high school graduation and the effect heterogeneity by educational background. No positive effect of participation is found. We discuss these results in relation to the potential of reducing inequalities by individual counseling in Germany. – – Cet article examine l'effet d'un programme de conseil intensif visant à promouvoir l'inscription des étudiants à l'université. A l'aide des données d'une étude expérimentale en longitudinale, nous examinons l'effet moyen de ce programme sur l'inscription à l'université directement après l'Abitur et l'hétérogénéité de l'effet selon le niveau d'éducation. Aucun effet positif de la participation n'est constaté. Ces résultats sont discutés en ce qui concerne le potentiel de réduction des inégalités du conseil individuel en Allemagne.
Keywords: 300; Studienaufnahme; Bildungsintervention; Experiment; soziale Herkunft; college access; educational intervention; experiment; social origin; accès au collège; intervention éducative; design expérimental; origine sociale